Physicochemical quality of eggplant dehydrated with varied pretreatments - doi: 10.4025/actascitechnol.v35i1.10551 - Osidacz, Rafael Chavez; Ambrósio-Ugri, Miriam Carla Bonicontro (Acta Scientiarum. Technology, 2012)
Among the main advantages of dehydrated fruit and vegetables are the great reduction of weight and volume, the ease of transport and storage, not requiring refrigeration, and a longer shelf-life compared with fresh products. This study analyzed the effect of bleaching and osmotic dehydration on the drying of eggplant slices, considering the quality parameters pH, titratable acidity, soluble solids, and shrinkage by image analysis. The pretreatments consisted of: (I) osmotic dehydration in 10% NaCl aqueous solution for 20 minutes at 35ÂºC; (II) bleaching of eggplant slices for 5 minutes followed by osmotic dehydration above cited. The pretreated eggplants were subjected to drying (70ÂºC), along with fresh eggplants, for further comparison. The results showed that the pretreated eggplants (bleached and osmotically dehydrated or osmotically dehydrated) have dried more rapidly than the control sample.